2008
DOI: 10.1007/s11869-008-0022-y
|View full text |Cite
|
Sign up to set email alerts
|

SO2 in Beirut: air quality implication and effects of local emissions and long-range transport

Abstract: While sulfur dioxide (SO 2 ) emissions have been dramatically restricted in the past few decades, some cities in developing countries still encounter high pollution levels. This makes it essential to implement an air quality monitoring network in these sensitive regions. Results from a program of measuring groundlevel concentration of SO 2 (from December 2004 till July 2006) at 22 curbside and background sites within the city of Beirut (Lebanon) are presented for the first time. Four-week sampling period measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 43 publications
1
5
2
Order By: Relevance
“…The average concentrations of NO x (0.095 ppm) in the present study was lower than that found in holy Makkah city, Saudi Arabia, during Hajj season 1425 H (0.15 ppm), (Al-Jeelani, 2009b) and much higher than those found in Al-Taneem area in the Holy Makkah city, Saudi Arabia (0.033 ppm), (Al-Jeelani, 2009a) The daily average concentrations of SO 2 (0.011 ppm) ( Fig. 1) was nearly similar to those found in Al-Taneem area in the Holy Makkah city, Saudi Arabia (0.010 ppm), (Al-Jeelani, 2009a) and in Ankara, Turkey (0.011 ppm), (DRSCH, 2006).On the other hand, the average concentrations of SO 2 in the present study was lower than those found in Dokki, Giza, Egypt (0.048 ppm) in winter and (0.032 ppm) in summer, (Khoder, 2002), in Dhaka, Bangladesh (0.045 ppm) (Gurjar et al, 2008) and in China (0.114 ppm), (Lei et al, 1997) and relatively lower than those found in Mexico City, Mexico (0.018 ppm), (Gurjar et al, 2008) and in Eskisehir, Turkey (0.018 ppm)\ (Özden et al, 2008) in Izmir, Turkey (0.015 ppm), (DRSCH, 2006) On the other hand, the average concentration of SO 2 in the current study was much higher than those found in Beirut, Lebanon (0.003 ppm), (Afif et al, 2008), in Roma, Italy (0.006 ppm) (Avino and Manigrasso, 2008), in Pamplona, Spain (0.003 ppm) (Zabalza et al, 2007) in Thurroch, UK (0.002 ppm), (UK Air Quality Archive, 2008) and relatively higher than that found in New York, USA (0.009 ppm) (USEPA, 2008) and in Beijing (0.009 ppm) (Wang et al, 2008) The daily average concentrations of O 3 (0.009 ppm) in this study were much lower than those found in Giza (Haram), Egypt, during the winter (0.030 ppm), spring (0.048 ppm), summer (0,064 ppm) and autumn (0.043 ppm), (Khoder, 2009), and in the city centre of Cairo, Egypt, (0.040, 0.058, 0.079, 0.051 ppm) during the corresponding seasons, respectively (Khoder, 2004), in Eskisehir, Turkey (0.019 and 0.027 ppm) during the winter (0.019 ppm) and in summer (0.027 ppm), (Özden et al, 2008) and in Al-Taneem area in the Holy Makkah city, Saudi Arabia (0.021 ppm), (Al-Jeelani, 2009a). In contrast SO 2 average concentration was higher than that found in the Holy Makkah city, Saudi Arabia during Hajj season 1425 H (0.004 ppm), (Al-Jeelani, 2009b).…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The average concentrations of NO x (0.095 ppm) in the present study was lower than that found in holy Makkah city, Saudi Arabia, during Hajj season 1425 H (0.15 ppm), (Al-Jeelani, 2009b) and much higher than those found in Al-Taneem area in the Holy Makkah city, Saudi Arabia (0.033 ppm), (Al-Jeelani, 2009a) The daily average concentrations of SO 2 (0.011 ppm) ( Fig. 1) was nearly similar to those found in Al-Taneem area in the Holy Makkah city, Saudi Arabia (0.010 ppm), (Al-Jeelani, 2009a) and in Ankara, Turkey (0.011 ppm), (DRSCH, 2006).On the other hand, the average concentrations of SO 2 in the present study was lower than those found in Dokki, Giza, Egypt (0.048 ppm) in winter and (0.032 ppm) in summer, (Khoder, 2002), in Dhaka, Bangladesh (0.045 ppm) (Gurjar et al, 2008) and in China (0.114 ppm), (Lei et al, 1997) and relatively lower than those found in Mexico City, Mexico (0.018 ppm), (Gurjar et al, 2008) and in Eskisehir, Turkey (0.018 ppm)\ (Özden et al, 2008) in Izmir, Turkey (0.015 ppm), (DRSCH, 2006) On the other hand, the average concentration of SO 2 in the current study was much higher than those found in Beirut, Lebanon (0.003 ppm), (Afif et al, 2008), in Roma, Italy (0.006 ppm) (Avino and Manigrasso, 2008), in Pamplona, Spain (0.003 ppm) (Zabalza et al, 2007) in Thurroch, UK (0.002 ppm), (UK Air Quality Archive, 2008) and relatively higher than that found in New York, USA (0.009 ppm) (USEPA, 2008) and in Beijing (0.009 ppm) (Wang et al, 2008) The daily average concentrations of O 3 (0.009 ppm) in this study were much lower than those found in Giza (Haram), Egypt, during the winter (0.030 ppm), spring (0.048 ppm), summer (0,064 ppm) and autumn (0.043 ppm), (Khoder, 2009), and in the city centre of Cairo, Egypt, (0.040, 0.058, 0.079, 0.051 ppm) during the corresponding seasons, respectively (Khoder, 2004), in Eskisehir, Turkey (0.019 and 0.027 ppm) during the winter (0.019 ppm) and in summer (0.027 ppm), (Özden et al, 2008) and in Al-Taneem area in the Holy Makkah city, Saudi Arabia (0.021 ppm), (Al-Jeelani, 2009a). In contrast SO 2 average concentration was higher than that found in the Holy Makkah city, Saudi Arabia during Hajj season 1425 H (0.004 ppm), (Al-Jeelani, 2009b).…”
Section: Resultscontrasting
confidence: 54%
“…In addition, atmospheric oxidation of SO 2 by hydroxide radical (OH), O 3 and hydrogen peroxide (H 2 O 2 ) contributes to acid deposition and sulfate formation (Finlayson-Pitts andPitts, 2000 andUSEPA, 2008).The major source of SO 2 is the combustion of fossil fuels containing sulfur, in particular from power stations burning coal and heavy fuel oil (Afif et al, 2008). Although road transport is a minor source of SO 2 at the national level, it can be important in some urban areas, especially alongside busy roads (Holgate et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…At 3 Km North of the site resides the Beirut harbor and at 8 km from its South-Western side, the international airport of Beirut is located. The main source of pollution in Beirut is vehicle traffic, the industrial activity being little developed in the surrounding city (Afif et al, 2008).…”
Section: Urban Sitementioning
confidence: 99%
“…Sulfurized copper ores are generally treated by flotation-smelting-refining [5][6][7]. Although they have reported economic [8] and metallurgical viability, there are environmental problems associated with the emission of sulfur dioxide and arsenic [9][10][11][12][13]. Arsenic, which has continuously increased in recent decades with the increasing extraction of copper sulfide [14], presents a risk to human health associated with a higher incidence of cancer and cardiovascular and respiratory diseases [15].…”
Section: Introductionmentioning
confidence: 99%